Disease of the past re-emerging in modern Australian society. Issue 4 (20th April 2019) - Uddin, Mohammed Arif; Robson, Christopher; Dotel, Ravindra
Abstract : A 28-year-old man with fever, atraumatic lower limb pain and rash was noted to have multiple areas of ecchymosis involving both lower limbs. He was anaemic and also had a grossly swollen left leg. Differential diagnoses of compartment syndrome, vascular tear, platelet and clotting factor disorders, vasculitis and myositis were ruled out. Scurvy was only considered after failing to reach a diagnosis. A dietary history revealed consumption of a restricted diet with no fresh fruits or vegetables. Diagnosis was supported by an undetectable vitamin C level in blood and a rapid improvement of symptoms on oral vitamin C replacement. Prevalence of vitamin C deficiency in developed countries is also discussed.